Ministry of Trade and Industry Decree No. 685 of the Year 2013 On Levying an Export Duty on the Exports of Nitrogenous Fertilizers = وزارة التجارة والصناعة قرار رقم 685 لسنة 2013 فى شأن فرض رسم صادر على الصادرات من الأسمدة الآزوتية - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic.